2007
DOI: 10.1105/tpc.107.051367
|View full text |Cite
|
Sign up to set email alerts
|

Increasing Plasma Membrane Phosphatidylinositol(4,5)Bisphosphate Biosynthesis Increases Phosphoinositide Metabolism inNicotiana tabacum

Abstract: A genetic approach was used to increase phosphatidylinositol(4,5)bisphosphate [PtdIns(4,5)P 2 ] biosynthesis and test the hypothesis that PtdInsP kinase (PIPK) is flux limiting in the plant phosphoinositide (PI) pathway. Expressing human PIPKIa in tobacco (Nicotiana tabacum) cells increased plasma membrane PtdIns(4,5)P 2 100-fold. In vivo studies revealed that the rate of 32 Pi incorporation into whole-cell PtdIns(4,5)P 2 increased >12-fold, and the ratio of [ 3 H]PtdInsP 2 to [ 3 H]PtdInsP increased 6-fold, b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
72
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(79 citation statements)
references
References 74 publications
(109 reference statements)
6
72
1
Order By: Relevance
“…Using transgenic tobacco (Nicotiana tabacum) cells expressing a mammalian PIP5K, it was recently shown that PIP5K is the flux-limiting factor in the plant metabolic pathway that leads to PtdIns(4,5)P 2 production (Im et al, 2007b). In our study, reduced PIP5K3 expression levels in the mutant lines or increased levels following inducible overexpression caused significantly shorter or longer root hairs, respectively, than normal.…”
Section: Discussionmentioning
confidence: 57%
“…Using transgenic tobacco (Nicotiana tabacum) cells expressing a mammalian PIP5K, it was recently shown that PIP5K is the flux-limiting factor in the plant metabolic pathway that leads to PtdIns(4,5)P 2 production (Im et al, 2007b). In our study, reduced PIP5K3 expression levels in the mutant lines or increased levels following inducible overexpression caused significantly shorter or longer root hairs, respectively, than normal.…”
Section: Discussionmentioning
confidence: 57%
“…Similar PI4P distribution was also found in root hairs (Vermeer et al, 2009). In plant cells, PI4P is the most abundant form of phosphoinositide (Im et al, 2007b). Genetic studies of enzymes involved in PI4P synthesis and degradation in root hairs have implicated PI4P in the regulation of polar exocytosis (Preuss et al, 2006;Thole et al, 2008).…”
Section: Pi4p May Participate In a Late Stage Of Clathrin-dependent Ementioning
confidence: 56%
“…Data previously published on the effects of pollen-expressed PLCs on polar tip growth (Dowd et al, 2006;Helling et al, 2006) indicate that a balance between synthesis and degradation of PtdIns(4,5) P 2 must be maintained for formation of the dynamic PtdIns(4,5)P 2 microdomain and for proper pollen tube elongation. In addition, data from in vivo labeling experiments indicate that PtdIns(4,5)P 2 is turned over very rapidly (Perera et al, 2002;Im et al, 2007;Krinke et al, 2007), and that increased abundance of PI4P 5-kinases should, thus, unbalance the system and have immediate effects on pollen tube growth.…”
Section: Discussionmentioning
confidence: 99%